¿LE DARÍAS A TU PROMETIDA UN ANILLO CUÁNTICO? - Duque, C. M.; Restrepo, R. L.; Morales, A. L.; Mora-Ramos, M. E.; Duque, C. A. (MOMENTO, 2013)
A quantum ring is a physical object similar to a real life ring that we find in our daily life, the only difference is in its very small nanometer dimensions (0.000000001 m). Furthermore, the ring is made of a semiconductor material called gallium arsenide (GaAs), as opposed to ordinary rings generally made of gold or silver. Another difference with the real ring is that it only has two dimensions, this means that it looks like a hole coin with negligible thickness. To the naked eye, this system could appear too ideal and not useful; but, these structures can be produced experimentally with very small thicknesses close to the system studied here and they have large enough important applications for the actual world.